Antifungal action on phytopathogens and activity of defense-related enzymes in wheat by propolis ethanolic extract (Research, Society and Development, 2025)
Propolis is widely known for its antimicrobial effects. Several studies have been aimed at understanding its effects on human health, but information on its use and mechanisms of action for controlling plant diseases is still limited. This study aimed to evaluate the action of propolis ethanolic extract (PEE) on wheat phytopathogens and the induction of defense-related enzymes in this crop. The antifungal activity was evaluated against the fungi that cause wheat diseases Pyricularia grisea (wheat blast), Fusarium graminearum (head blight), Bipolaris sorokiniana (spot blotch), and Puccinia triticina (rust). Concentrations of 0, 0.1, 0.5, 1, and 2% of PEE were evaluated. In a greenhouse experiment, the activity of peroxidases and polyphenoloxidases was evaluated in wheat plants subjected to application of concentrations of 0, 0.1, 0.5, 1, and 2% PEE at 0, 24, 48, 72, and 96 hours after application. PEE showed a dose-dependent inhibitory effect on all fungi tested, although there was no complete inhibition of growth. For peroxidases and polyphenoloxidases, there was no significant effect (p